A challenge finding P2X1 and P2X4 ligands. (October 2019) - Beswick, Paul; Wahab, Ben; Honey, Mark A.; Paradowski, Michael; Jiang, Ke; Lochner, Martin; Murrell-Lagnado, Ruth D.; Thompson, Andrew J.
Abstract: Identifying novel small-molecule P2X1 and P2X4 ligands with sub-type specificity and high-affinity remains a pharmacological challenge. Here we use computational methods, electrophysiology and fluorescent microplate assays to screen for ligand candidates acting at these receptors. Modelling and docking identified 80 compounds for testing at P2X4 receptors, and 20 of these showed >50% inhibition in fluorescence-based assays, making them appealing for further SAR studies. Confirmation of activity by two-electrode voltage clamp, followed by their elaboration resulted in only minor improvements in potency, with the highest IC 50 being 295 μM. Testing on P2X1 receptors, resulted in a series of biguanide compounds that yielded a maximum IC 50 of 100 μM, but no consistent SAR could be found. Potencies of established antagonists gave expected results, although the measured potencies varied between techniques and no antagonism could be found for compounds such as paroxetine, carbamazepine, 9(10 H )-acridanone, acridinol and phenoxazine-type heterocycles. This study highlights the challenge of identifying P2X4 and P2X1 ligands and suggests that a combination of complimentary approaches is needed if we are to be confident of ligand activities at these receptors. Graphical abstract: Image 1 Highlights: We aimed to identify novel P2X1 and P2X4 receptor ligands. We used a combination if in silico screening, fluorescence and two-electrode voltage clamp. Only minor improvements in potency were achieved. We highlight the challenge of identifying compounds that target this receptor class. We suggest that at least two complimentary approaches are needed to confirm novel hits.